Effect of light, sodium hypochlorite, scarification, and stratification on seed germination of lettuce (Lactuca sativa L), cv. "Maioba" and "Moreninha-de-Uberlândia" - Carnelossi, Marcelo A.G.; Lamounier, Lucivane; Ranal, Marli A. (Pesquisa Agropecuaria Brasileira, 1995)
The cultivars of lettuce "Maioba" and "Moreninha-de-Uberlândia" are vegetables of economic and nutritive potential with a high content of A and C vitamins. Information about the factors that interfere on the seed germination of these cultivars can be used to obtain a great number of seedlings for a production in commercial scale. The seeds were submitted to 16 treatments with 5 replicates of 50 seeds each one. The seeds were cultivated between 21 and 24 oC, at 2088.38 µW/cm2 of average irradiance. The seeds of the two cultivars are positively photoblastic, but "Moreninha-de-Uberlândia" is more dependent on light than "Maioba." This sensibility and dependence of light disappeared in older seeds of the cv. "Moreninha-de-Uberiândia". The sodium hypochlorite inhibited and retarded for 16 days the germination process of seeds with 101 days of age, while for older seeds of this cultivar sensibility to sodium hypochlorite disappeared. The stratification accelerated the germination for this cultivar in relation to the other treatments. However, this treatment failed to accelerate the germination of seeds of the cv. "Maioba".
Keywords: germinability; storage; asepsis; photoblastism